Religion and the gender vote gap: Women's changed political preferences from the 1970s to 2010 - Philip Manow; Patrick Emmenegger (Universität Bremen, Zentrum für Sozialpolitik (ZeS), 2012)
For many years women tended to vote more conservative than men (the 'old' gender vote gap), but since the 1980s this gap in many countries has shifted direction: now women in many countries are more likely to support left parties than men of the same age, in the same income bracket, and at the same educational level (the 'new' gender vote gap). The literature largely agrees on a set of political-economic factors explaining the change in women's political orientation: changed employment patterns, women's higher educational achievements, and higher divorce rates. These trends turned women into supporters of generous social programs that promise to 'de-familialize' services formerly provided privately within the family. In this paper, we demonstrate that these conventional political-economic factors fall short in explaining the old gender vote gap. We may therefore also harbor doubts whether they provide us with a full story for the new gender vote gap. Instead, we highlight the importance of religion for the gendered pattern of voting behavior that we observe. We argue that where vote choice expressed preferences on a non-economic, i.e. mainly religious issue dimension, parties in the past could afford - at least to some extent - ignoring voters' socio-economic interests. Given that surveys show us a constantly higher degree of religiosity among women and a relatively persistent and strong impact of religion on vote choice, religion can indeed, we argue, explain a substantial part of the old and new gender vote gap.
Keywords: 300; Wahlverhalten; Geschlecht; Religion; EU-Staaten